Micro insights on the pathways to agricultural transformation: Comparative evidence from Southeast Asia and Sub-Saharan Africa - Amare, Mulubrhan; Parvathi, Priyanka; Trung Thanh Nguyen (Wiley, 2023)
Most studies of agricultural transformation document the impact of agricultural income growth on macroeconomic indicators of development. Much less is known about the micro-scale changes within the farming sector that signal a transformation precipitated by agricultural income growth. This study provides a comparative analysis of the patterns of micro-level changes that occur among small-holder farmers in Uganda and Malawi in Sub-Saharan Africa (SSA), and Thailand and Vietnam in Southeast Asia (SEA). Our analysis provides several important insights on agricultural transformation in these two regions. First, agricultural income in all examined countries is vulnerable to changes in precipitation and temperature, an effect that is nonlinear and asymmetric. SSA countries are more vulnerable to these weather changes. Second, exogenous increases in agricultural income in previous years improve non-farm income and trigger a change in labor allocation within the rural sector in SEA. However, this is the opposite in SSA where the increase in agricultural income reduces non-farm income, indicating a substitution effect between farm and non-farm sectors. These findings reveal clear agricultural transformation driven by agricultural income in SEA but no similar evidence in SSA.